Evidence for the Minoan Language - Gordon, Cyrus H. (1966)
Introduction – Eteocypriote – The Eteocretan Texts – The Development and Transmission of the Alphabet on Crete – Eteocretan Orthography – Eteocretan Phonetics – Eteocretan Morphology – The Decipherment of Minoan – Names in the Minoan Texts – Minoan Orthography – Minoan Phonetics – Minoan Morphology – Index of Minoan Words and Names Cited – The Phaistos Disc – Minoan Origins; $6.